2021
DOI: 10.3389/fcimb.2021.679792
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Residues in the MK-Rich Region Are Not Required for Binding of the PbsP Protein From Group B Streptococci to Plasminogen

Abstract: Binding to plasminogen (Plg) enables bacteria to associate with and invade host tissues. The cell wall protein PbsP significantly contributes to the ability of group B streptococci, a frequent cause of invasive infection, to bind Plg. Here we sought to identify the molecular regions involved in the interactions between Plg and PbsP. The K4 Kringle domain of the Plg molecule was required for binding of Plg to whole PbsP and to a PbsP fragment encompassing a region rich in methionine and lysine (MK-rich domain).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…One of the most studied TCS in GBS is the CovRS regulatory system where the sensor histidine kinase CovS senses external signals and activates the response regulator CovR [ 220 ]. This system directly or indirectly regulates the expression of different genes [ 221 ], including those encoding virulence factors, such as β-hemolysin/cytolysin (β-h/c) [ 222 ], HvgA [ 223 ], PbsP [ 209 , 224 , 225 , 226 ], and other ones. Furthermore, pbsP is subjected to the transcriptional regulation mediated by the recently discovered SaeRS TCS that greatly enhances its expression by rendering GBS more virulent in vivo [ 216 ].…”
Section: Two-component Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most studied TCS in GBS is the CovRS regulatory system where the sensor histidine kinase CovS senses external signals and activates the response regulator CovR [ 220 ]. This system directly or indirectly regulates the expression of different genes [ 221 ], including those encoding virulence factors, such as β-hemolysin/cytolysin (β-h/c) [ 222 ], HvgA [ 223 ], PbsP [ 209 , 224 , 225 , 226 ], and other ones. Furthermore, pbsP is subjected to the transcriptional regulation mediated by the recently discovered SaeRS TCS that greatly enhances its expression by rendering GBS more virulent in vivo [ 216 ].…”
Section: Two-component Systemsmentioning
confidence: 99%
“…Furthermore, pbsP is subjected to the transcriptional regulation mediated by the recently discovered SaeRS TCS that greatly enhances its expression by rendering GBS more virulent in vivo [ 216 ]. Studies on SaeRS correlation with pbsP are currently underway among different clonotypes and in other in vivo infection models, given the importance of this adhesin in GBS pathogenesis [ 209 , 224 , 225 , 226 ].…”
Section: Two-component Systemsmentioning
confidence: 99%
“…Amino acids are the important molecules in human body, and its main role is as components of proteins ( Das et al., 2020 ; Farag et al., 2020 ; Hegazi et al., 2020 ; Coppolino et al., 2021 ). However, they are also involved in many important biological functions, such as i) provide energy and ii) serve as neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated both direct and indirect interactions of GBS with integrins. For example, these bacteria can invade respiratory cells by using the Plasminogen binding surface Protein (PbsP) cell wall adhesin to bind vitronectin, which acts as a bridge to activate the α v integrins (Buscetta et al, 2016 ; De Gaetano et al, 2018 ; Lentini et al, 2018 ; Coppolino et al, 2021 ). Direct GBS-integrin interactions have also been documented (Cuzzola et al, 2000 ; Bolduc and Madoff, 2007 ).…”
Section: Introductionmentioning
confidence: 99%